What are we protecting? An analysis of the current conservation framework addressing Mediterranean mesophotic habitats - Castellan, G.; Abbiati, M.; Angeletti, L.; Foglini, F.; Grande, V.; Montagna, P.; Taviani, M. (Frontiers in Environmental Science, 2022)
Mesophotic ecosystems in the Mediterranean Sea are biodiversity hotspots distributed from ca 30 m down to 180 m, depending upon the depth of light compensation point. Overall, the taxonomic composition of Mediterranean mesophotic ecosystems is dominated by corals and sponges, with subordinate bryozoans, mollusks, ascidians, stony corals and shade-adapted algae. As for most marine ecosystems, the mesophotic habitats are increasingly exposed to natural and anthropogenic threats, including seawater temperature rise, more intense and frequent heat waves, progressive ocean acidification, fishing activities and littering. The establishment of effective governance guidelines is, therefore, the necessary rationale to guarantee the good environmental status of such widespread, highly diverse, service-provider natural resources. However, an in-depth quantification of the extent to which Mediterranean mesophotic habitats and taxa are included in conservation measures is lacking. We have reviewed available literature information on mesophotic habitats in the Mediterranean Sea to evaluate the efficiency of the current legislative framework in providing instruments to protect this natural heritage. Our analysis allows identifying gaps in the current conservation network, ultimately suggesting functional integrative actions for effective conservation measures and the long-term survival of Mediterranean mesophotic ecosystems.